On log-logistic and a four-parameter generalized log-logistic distributions - Olapade, A. K. (2014)
In this paper, we obtained the distribution of some functions of log-logistic random variables and derived a probability density function that generalizes the distribution. The cumulative distribution function, the nth moment, the median, the mode and the 100k-percentage points of the new generalized distribution are established. Two theorems that relate the non- generalized distribution to other statistical distributions are stated and proved.